Uncertainty in suspended sediment load estimates for mountain rivers: Case of study of central andes in Perú - Morera-Julca, Sergio (2013)
This study evaluates the uncertainty in the estimation of annual and monthly sediment flows in four mountain basins of the Pacific Ocean in Peru. For this end, samples at different time scales (hourly, daily, and monthly) were recorded. The database was broken down into a numerical base to simulate several sampling frequencies. From these timing frequencies, the annual and monthly flow was computed. Likewise, we compare the observed and simulated data, calculating the degree of uncertainty using statistical tests. The results for the 25 and 75 percentiles show that there is a high temporal variability in these Andean watersheds, whose strategy of measurement of solid flows can vary from six to 12 days, thus underestimating ~ 20% annually. While for estimating suspended sediment yield (SY) to a monthly time step in the rainy season (December to May), a sampling frequency between 1-5 days, which would lead to a maximum error of ± 40% being needed. However, for the dry season (June to September), the sampling can be done one time per month for an error of ± 45%, which is less than 2% in an annual balance. Finally, the results show that the sampling frequency values mentioned above should be reduced to half, for exceptional events (rainy season) where the annual error estimate is around 300%.